2018
DOI: 10.18203/2349-3291.ijcp20181514
|View full text |Cite
|
Sign up to set email alerts
|

A study of immunization status of children in the age group 2-5 years

Abstract: Background: An evaluation by UNICEF India coverage survey (2009) showed that in India, 61% of children are fully immunized which is significantly low. Objectives of this study were to determine Immunization status of children in the age group of 2 to 5 years and study the social factors influencing immunization status of a child. To know the reasons for partial and non-immunization and study relation of socio-economic status with immunization status.Methods: A total 2000 children aged 2-5 years who are attendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
4
7
0
Order By: Relevance
“…8 In the present study 35.9% children were due for LPV 3 and OPV 3, 28.1% children were due for LPV 2 OPV 2, 7.8% children were due for LPV 1 and OPV 1. These findings were similar to the findings of Kurane et al 9 Birth to DPT 1ST dose overall has 42% drop out. So, progressive increase in the missing the dose of LPV2 and LPV3 is because of unawareness of subsequent doses, Fear of AEFI and sickness status of the child.…”
Section: Discussionsupporting
confidence: 91%
“…8 In the present study 35.9% children were due for LPV 3 and OPV 3, 28.1% children were due for LPV 2 OPV 2, 7.8% children were due for LPV 1 and OPV 1. These findings were similar to the findings of Kurane et al 9 Birth to DPT 1ST dose overall has 42% drop out. So, progressive increase in the missing the dose of LPV2 and LPV3 is because of unawareness of subsequent doses, Fear of AEFI and sickness status of the child.…”
Section: Discussionsupporting
confidence: 91%
“…Because of that they are not ready for vaccinate their children, that leads to the risk of their own child's life. (5) During the survey, it was revealed that the parents had good knowledge regarding Universal immunization program but limited awareness of the knowledge towards newer vaccines as well as optional vaccination. (6) The main reason of Immunization delayed was due to lack of family support, poor participation of the male as well as negative attitude of the elderly at home, gender bias, common childhood illness, apprehension of giving many vaccines at one time and adverse rumours.…”
Section: Discussionmentioning
confidence: 99%
“…Among the individual vaccines, it was found that the immunization status for BCG & OPV-0 was highest, which was similar to the findings from most of the other studies. [17][18][19][20][21] These are the vaccines given at the time of birth, and the highest percentage of vaccination for these is justified as institutional delivery was reported by most, i.e., at Government and private hospitals. Immunization status for subsequent vaccines showed a downtrend.…”
Section: Discussionmentioning
confidence: 99%